Comparison of push-in and push-out tests for measuring interfacial shear strength in nano-reinforced composite materials. (May 2016) - Medina M, Carlos; Molina-Aldareguía, Jon M; González, Carlos; Melendrez, Manuel F; Flores, Paulo; LLorca, Javier
The influence of the carbon nanotubes (CNTs) content on the fiber/matrix interfacial shear strength (IFSS) in glass/fiber epoxy composites was measured by means of push-in and push-out tests. Both experimental methodologies provided equivalent values of the IFSS for each material. It was found that the dispersion of CNTs increased in IFSS by 19% in average with respect to the composite without CNTs. This improvement was reached with 0.3 wt.% of CNTs and increasing the CNT content up to 0.8 wt.% did not improve the interface strength.